PENGARUH PENGGUNAAN TRAKTOR TERHADAP TEGAKAN TINGGAL PADA BEBERAPA PENGUSAHAAN HUTAN DI KALIMANTAN TIMUR - Jurnalis Thaib (Pusat Penelitian dan Pengembangan Hasil Hutan, 1985)
The damage to residual stands as a result of tractor logging is evaluated. In 10 concessions in East Kalimantan, the number of trees felled per hectare was corelated with the percent decrease in the number of residual trees (20 cm and up) per hectare.The results indicated that increasing the number of trees felled per hectare caused greater decrease in the percentage of residual trees (20 cm and up).A better logging plan including strict adherence to the TPI (Indonesian Selective Logging) regulations, pre-laid skidding roads and tree location plan is recommended to reduce the damage to residual stands.